2016
DOI: 10.1089/hs.2016.0005
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance for Emerging Diseases with Multiplexed Point-of-Care Diagnostics

Abstract: We present an analysis of the diagnostic technologies that were used to identify historical outbreaks of Ebola virus disease and consider systematic surveillance strategies that may greatly reduce the peak size of future epidemics. We observe that clinical signs and symptoms alone are often insufficient to recognize index cases of diseases of global concern against the considerable background infectious disease burden that is present throughout the developing world. We propose a simple sampling strategy to enr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Novel technology (paper-based or smartphone-based) with enhanced accuracy, portability, and response can reduce the TTAT to care and costs in decentralized health settings [ 73 ]. Multiplex molecular diagnostics for infectious diseases utilize large test clusters to screen for various pathogens and avoid substantial delays in TTAT to treatment and improve patient health outcomes [ 74 ]. Upstream shift via SCP TM .…”
Section: Discussionmentioning
confidence: 99%
“…Novel technology (paper-based or smartphone-based) with enhanced accuracy, portability, and response can reduce the TTAT to care and costs in decentralized health settings [ 73 ]. Multiplex molecular diagnostics for infectious diseases utilize large test clusters to screen for various pathogens and avoid substantial delays in TTAT to treatment and improve patient health outcomes [ 74 ]. Upstream shift via SCP TM .…”
Section: Discussionmentioning
confidence: 99%
“…Novel technology (paper-based, smartphone-based) with enhanced accuracy, portability, and response can reduce the TTAT to care and costs in decentralized health settings [72]. Multiplex molecular diagnostics for infectious diseases utilize large test clusters to screen for various pathogens and avoid substantial delays in TTAT to treatment and improve patient health outcomes [73].…”
Section: Discussionmentioning
confidence: 99%
“…In countries where CQ use was discontinued, studies have shown that, in the absence of drug pressure, CQ-resistant strains of P. falciparum have been replaced by CQ-sensitive isolates [ 10 ]. Therefore, the development of CQ analogues as multi-species antimalarial agents may still be valid and has been recently highlighted and reviewed [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%